Lithium manganese phosphate precursor, positive electrode material and preparation method of positive electrode material
By using gradient co-doped manganese oxalate precursor and high-conductive carbon network in lithium manganese phosphate positive electrode material, the problem of insufficient electronic conductivity and lithium ion diffusion ability is solved, and the electrochemical performance and cyclic performance are significantly improved, satisfying the The demand for high-energy density lithium-ion batteries.
Patent Information
- Application Number
- CN202411414583.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-14
AI Technical Summary
The electronic conductivity and lithium ion diffusion ability of the lithium manganese phosphate cathode material are limited by structural limitations, resulting in its low electrochemical performance and cannot meet the needs of high-energy-density lithium-ion batteries.
The gradient co-doped manganese oxalate precursor is used to gradually reduce the cobalt ion content from the inside to the outside along the lithium manganese phosphate particles and increase the aluminum ion content, combined with a high-conductive carbon network, and prepare a gradient co-doped lithium manganese phosphate positive electrode material. Improve its conductive properties and structural stability.
It significantly improves the diffusion rate and electron conduction ability of lithium ions, enhances the cycling performance of the material and battery capacity, and achieves the improvement of electrochemical performance.
Smart Images

Figure CN119306593A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a lithium manganese phosphate precursor, a positive electrode material and a method for preparing the positive electrode material. Background Art
[0002] In recent years, with the iteration and upgrading of technology, the continuous improvement of the energy density of lithium iron batteries and the large-scale application of module-free CTP, the battery life of lithium iron phosphate batteries has been greatly improved, making up for the shortcoming of low battery life; lithium iron phosphate batteries have rapidly increased their market share and become the mainstream of the market due to their low cost, excellent safety performance and long cycle life.
[0003] The cathode material of lithium-ion batteries is a key factor affecting battery performance. The working voltage of commercialized cathode material lithium iron phosphate is relatively low and cannot meet the use requirements of high energy density lithium-ion batteries. Like lithium iron phosphate batteries, lithium manganese phosphate is also an olivine-type phosphate-based lithium battery cathode material. The safety and cycle life of this material are higher than those of traditional layered cathode materials lithium cobalt oxide and ternary materials. However, the 3.4V potential of the widely used lithium iron phosphate limits the improvement of battery energy density, while lithium manganese phosphate has a high potential of 4.1V. Therefore, under the same capacity, the energy density of lithium manganese phosphate batteries can be increased by about 20% compared with lithium iron phosphate batteries. As a hot research topic for cathode materials today, olivine-type lithium manganese phosphate has the advantages of low cost, low toxicity, good cycle performance, stable structure, and high energy intensity. However, similar to lithium iron phosphate materials, lithium manganese phosphate materials are affected by their own structure, and their electronic conductivity and lithium ion diffusion capacity are severely limited.
[0004] Therefore, improving the electrochemical properties of lithium manganese phosphate and improving its synthesis method are the research focuses in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a gradient co-doped manganese oxalate precursor, and to prepare an excellent lithium manganese phosphate positive electrode material using the material. The specific scheme is as follows:
[0006] A lithium manganese phosphate precursor, wherein the lithium manganese phosphate precursor has a chemical formula of Mn 1-x-y Co x Al y C2O4·2H2O, 0.01≤x≤0.05, 0.01≤y≤0.05; the lithium manganese phosphate precursor is doped with cobalt ions and aluminum ions, and along the manganese oxalate particles from the inside to the outside, the content of cobalt ions gradually decreases, and the content of aluminum ions gradually increases.
[0007] The general chemical formula of the lithium manganese phosphate positive electrode material is Mn 1-x-y Co x Aly PO4 / C, 0.01≤x≤0.05, 0.01≤y≤0.05; the lithium manganese phosphate positive electrode material is doped with cobalt ions and aluminum ions, and along the lithium manganese phosphate particles from the inside to the outside, the content of cobalt ions gradually decreases, and the content of aluminum ions gradually increases.
[0008] The total mass of lithium manganese phosphate and carbon is 100wt%, and the content of carbon is 3% to 9%.
[0009] A method for preparing a lithium manganese phosphate positive electrode material, comprising the following steps:
[0010] (1) preparing a Mn source, an Al source, a Co source and an oxalic acid solution;
[0011] (2) adding the Mn source and the oxalic acid solution into a reaction container filled with inert gas at a fixed flow rate, while the injection flow rate of the Co source solution is gradually reduced and the injection flow rate of the Al source solution is gradually increased to perform a co-precipitation reaction to obtain a mixed slurry;
[0012] (3) separating the slurry to obtain a filter cake, and drying it;
[0013] (4) dry-mixing the dried precursor with a carbon source, a lithium source, and a phosphorus source, and calcining the mixture to obtain an Al and Co gradient co-doped lithium manganese phosphate positive electrode material.
[0014] The Mn source is selected from one or more of manganous nitrate, manganous sulfate and manganous chloride, and the concentration of the manganese source solution is 1-3.0 mol / L; the molar ratio of the oxalic acid solution to the Mn source solution is 1-1.2:1.
[0015] The total amount of Mn source or oxalic acid solution is S1, and the injection rate into the reactor is V1. The total amount of Co source or Al source solution is S2. Then the Co source solution is injected at an initial flow rate of V2. The amplitude decreases linearly, and the Al source solution is injected at an initial flow rate of 0. The amplitude increases linearly, 10mL / min≤V1≤50mL / min, 1.8L≤S1≤9L, 0.3L≤S2≤0.9L.
[0016] In step (4), the carbon source includes a composite of an organic carbon source and an inorganic carbon source, the inorganic carbon source includes one or more carbon materials in the form of graphene, carbon nanotubes, acetylene black, graphite, carbon black, etc., and the organic carbon source includes one or more of glucose, sucrose, starch, citric acid, polyethylene glycol, phenolic resin, and polydopamine.
[0017] In step (4), the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium oxalate, and lithium dihydrogen phosphate, and the phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate, ammonium monohydrogen phosphate, and lithium dihydrogen phosphate.
[0018] In step (4), the dry mixed powder is placed in a tube furnace and calcined in two steps in an atmosphere of high purity nitrogen.
[0019] The specific steps of the two-step calcination are as follows: pre-calcination: heating from room temperature to 350-500°C at 5°C / min, keeping warm for 4-8h, cooling to room temperature and taking out; grinding: grinding in a mortar with anhydrous ethanol until the powder is uniform, and drying; re-calcination: heating from room temperature to 600-700°C at 5°C / min, keeping warm for 7-10h, and obtaining a sample after cooling.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention dopes Co ions into the manganese oxalate precursor, thereby doping Co ions into the finally synthesized lithium manganese phosphate, and the content of Co ions gradually decreases from the inside to the outside of the lithium manganese phosphate particles. Co element doping can reduce the migration barrier, increase the diffusion rate of lithium ions, and further improve its electrical conductivity, which is also beneficial to the performance of the material capacity.
[0022] (2) Similarly, the present invention adopts Al element doping, and the content gradually increases from the inside to the outside of the lithium manganese phosphate particles. This is because Al is doped into the outer layer as an inert element, which can significantly alleviate the irreversible phase change, thereby inhibiting the generation of microcracks, enhancing structural stability, and thus improving the cycle capacity.
[0023] (3) The present invention controls and adjusts the preparation method during the precursor synthesis process, thereby synthesizing gradient-doped Al and Co in the precursor, thereby ensuring the presence of gradient-doped elements in the lithium manganese phosphate positive electrode, and through the synergistic effect of the high-conductive carbon network, when preparing the lithium manganese phosphate positive electrode material, efficient conduction of electrons and ions can be achieved, thereby improving the capacity and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD pattern of the gradient co-doped manganese oxalate precursor prepared in Example 1;
[0025] Figure 2 This is the XRD pattern of the gradient co-doped lithium manganese phosphate positive electrode material prepared in Example 1;
[0026] Figure 3 This is the SEM image of the gradient co-doped manganese oxalate precursor prepared in Example 1. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0028] Example 1
[0029] According to LiMn 0.94 Co 0.03 Al 0.03 PO4 stoichiometric ratio, prepare 6L 2mol / L MnSO4 solution, 6L 2.1mol / L oxalic acid solution, 0.6L 0.638mol / L CoSO4 solution, 0.6L 0.638mol / L Al(NO3)3 solution;
[0030] After the reaction vessel is filled with inert nitrogen, the MnSO4 solution and oxalic acid solution are injected into the reaction vessel at a rate of 20 mL / min. At the same time, the Co source solution is injected at an initial flow rate of 4 mL / min and then at a rate of 0.013 mL / min. 2 The amplitude of the linear decrease, Al source solution was injected at an initial flow rate of 0, and then at 0.013mL / min 2 The amplitude increases linearly, and a coprecipitation reaction is carried out to obtain a mixed slurry;
[0031] After the coprecipitation reaction, centrifugation, washing and filtering are performed multiple times to obtain a filter cake, which is then dried in a dryer;
[0032] Weigh 1 mol of Mn 0.94 Co 0.03 Al 0.03 C2O4·2H2O, 1 mol of LiH2PO4, 3.14 g of graphene and 20.41 g of glucose were added and dry mixed for 1 hour. The dry mixed powder was placed in a tube furnace and sintered in two steps in a high-purity nitrogen atmosphere:
[0033] Pre-burning: heat from room temperature to 450℃ at 5℃ / min, keep warm for 5h, cool to room temperature and take out;
[0034] Grinding: Grind in a mortar with anhydrous ethanol until the powder is uniform and dry;
[0035] Re-firing: Raise the temperature from room temperature to 680°C at 5°C / min, keep warm for 8h, and obtain the sample after cooling.
[0036] Example 2
[0037] The difference from Example 1 is that according to LiMn 0.94 Co 0.04 Al 0.02 PO4 is dosed in a stoichiometric ratio.
[0038] Example 3
[0039] The difference from Example 1 is that according to LiMn 0.94 Co 0.02 Al 0.04 PO4 is dosed in a stoichiometric ratio.
[0040] Example 4
[0041] The difference from Example 1 is that CNT is replaced by graphene.
[0042] Comparative Example 1
[0043] The difference from Example 1 is that Co ions and Al ions are not doped.
[0044] Comparative Example 2
[0045] The difference from Example 1 is that Co ions and Al ions are injected into the reactor at a constant flow rate of 2 mL / min.
[0046] Comparative Example 3
[0047] The difference from Example 1 is that no highly conductive CNTs are added.
[0048] Weigh the prepared active material, acetylene black and PVDF according to the mass ratio of 8:1:1, mix and grind them evenly in a mortar, add an appropriate amount of NMP and continue grinding until a uniformly mixed slurry is obtained, spread the aluminum foil on a clean glass plate, and use a four-sided wet film preparation device (the coating thickness specification is 250μm) to apply the slurry on the aluminum foil to form a pole piece with uniform thickness, and dry it in a vacuum drying oven at 120℃ for 6 hours. Use a button battery punching machine to prepare slices, punch the pole piece into a pole piece with a diameter of 14mm, and assemble it in the order of negative electrode shell, lithium sheet, diaphragm, positive electrode sheet, gasket, spring sheet and positive electrode shell. Add an appropriate amount of electrolyte during the process, and finally package the battery on the packaging machine, and perform battery charge and discharge tests. The test results are shown in Table 1 below.
[0049] Table 1 Performance test results
[0050]
[0051] Figure 1 The XRD pattern of the manganese oxalate precursor prepared in Example 1 matches well with the PDF#23-0293 standard card, and no obvious impurity peak is found. By observing the intensity of the diffraction peak, the crystallinity of the synthesized material is relatively high. Figure 2This is the XRD pattern of the sample prepared in Example 1. By comparing with the PDF#98-016-7253 card, it can be seen that the prepared sample has an olivine structure and belongs to the Pnmb space point group. The main crystal plane diffraction peaks of the sample, such as (011), (021), (200), (031), (131), etc., correspond well to the standard spectrum. The diffraction peaks are sharp and there is no impurity peak, indicating that the prepared sample has good crystallinity.
[0052] Figure 3 The manganese oxalate precursor prepared in Example 1 was tested by SEM. As shown in the figure, the material synthesized by the co-precipitation method showed a polyhedral columnar structure with a length of about 10 μm and uniform dispersion.
[0053] It can be seen from Table 1 that the electrical properties of Examples 1-4 are significantly improved compared to Comparative Examples 1-3. This is because the conductivity and cycle stability of the positive electrode active material can be improved simultaneously by gradient co-doping of Co and Al ions in this application. At the same time, because the two metal ions have a synergistic effect, combined with the construction of a highly conductive network CNT or graphene, efficient conduction of electrons and ions can be achieved when preparing the lithium manganese phosphate positive electrode material, thereby improving the capacity and cycle performance of the battery.
[0054] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent replacements or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A lithium manganese phosphate precursor, characterized in that: The general chemical formula of the lithium manganese phosphate precursor is Mn 1-x- y Co x Al y C2O4·2H2O, 0.01≤x≤0.05, 0.01≤y≤0.05; the lithium manganese phosphate precursor is doped with cobalt ions and aluminum ions, and along the manganese oxalate particles from the inside to the outside, the content of cobalt ions gradually decreases, and the content of aluminum ions gradually increases.
2. A lithium manganese phosphate positive electrode material, characterized in that: The chemical formula of the lithium manganese phosphate positive electrode material is Mn 1-x- y Co x Al y PO4 / C, 0.01≤x≤0.05, 0.01≤y≤0.05; the lithium manganese phosphate positive electrode material is doped with cobalt ions and aluminum ions, and along the lithium manganese phosphate particles from the inside to the outside, the content of cobalt ions gradually decreases, and the content of aluminum ions gradually increases.
3. A lithium manganese phosphate positive electrode material as claimed in claim 2, characterized in that: The total mass of lithium manganese phosphate and carbon is 100wt%, and the content of carbon is 3% to 9%.
4. A method for preparing the lithium manganese phosphate positive electrode material as claimed in claim 2, characterized in that: Here are the steps: (1) preparing a Mn source, an Al source, a Co source and an oxalic acid solution; (2) adding the Mn source and the oxalic acid solution into a reaction container filled with inert gas at a fixed flow rate, while the injection flow rate of the Co source solution is gradually reduced and the injection flow rate of the Al source solution is gradually increased to perform a co-precipitation reaction to obtain a mixed slurry; (3) separating the slurry to obtain a filter cake, and drying it; (4) dry-mixing the dried precursor with a carbon source, a lithium source, and a phosphorus source, and calcining the mixture to obtain an Al and Co gradient co-doped lithium manganese phosphate positive electrode material.
5. A method for preparing a lithium manganese phosphate positive electrode material as claimed in claim 4, characterized in that: The Mn source is selected from one or more of manganous nitrate, manganous sulfate and manganous chloride, and the concentration of the manganese source solution is 1-3.0 mol / L; the molar ratio of the oxalic acid solution to the Mn source solution is 1-1.2:
1.
6. A method for preparing a lithium manganese phosphate positive electrode material as claimed in claim 4, characterized in that: The total amount of Mn source or oxalic acid solution is S1, and the injection rate into the reactor is V1. The total amount of Co source or Al source solution is S2. Then the Co source solution is injected at an initial flow rate of V2. The amplitude decreases linearly, and the Al source solution is injected at an initial flow rate of 0. The amplitude increases linearly, 10mL / min≤V1≤50mL / min, 1.8L≤S1≤9L, 0.3L≤S2≤0.9L.
7. A method for preparing a lithium manganese phosphate positive electrode material as claimed in claim 4, characterized in that: In step (4), the carbon source includes a composite of an organic carbon source and an inorganic carbon source, the inorganic carbon source includes one or more carbon materials in the form of graphene, carbon nanotubes, acetylene black, graphite, carbon black, etc., and the organic carbon source includes one or more of glucose, sucrose, starch, citric acid, polyethylene glycol, phenolic resin, and polydopamine.
8. A method for preparing a lithium manganese phosphate positive electrode material as claimed in claim 4, characterized in that: In step (4), the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium oxalate, and lithium dihydrogen phosphate, and the phosphorus source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate, ammonium monohydrogen phosphate, and lithium dihydrogen phosphate.
9. A method for preparing a lithium manganese phosphate positive electrode material as claimed in claim 4, characterized in that: In step (4), the dry mixed powder is placed in a tube furnace and calcined in two steps in an atmosphere of high purity nitrogen.
10. A method for preparing a lithium manganese phosphate positive electrode material as claimed in claim 9, characterized in that: The specific steps of the two-step calcination are as follows: pre-calcination: heating from room temperature to 350-500°C at 5°C / min, keeping the temperature for 4-8h, cooling to room temperature and taking out; Grinding: Grind in a mortar with anhydrous ethanol until the powder is uniform, and dry; Re-firing: Raise the temperature from room temperature to 600-700°C at 5°C / min, keep warm for 7-10 hours, and obtain the sample after cooling.
Citation Information
Patent Citations
Lithium manganese phosphate positive pole material and preparation method thereof
CN102694168A
Gradient-doped manganese iron oxalate precursor and preparation method thereof
CN104710302A
Doped lithium iron manganese phosphate positive electrode material, preparation method thereof, positive electrode plate containing doped lithium iron manganese phosphate positive electrode material, and lithium ion battery containing doped lithium iron manganese phosphate positive electrode material
CN116741987A